Ultrathin Two-Dimensional Polyoxometalate-Based Metal–Organic Framework Nanosheets for Efficient Electrocatalytic Hydrogen Evolution - Wang, Lei; Wang, Ani; Xue, Zhen-Zhen; Hu, Ji-Xiang; Han, Song-De; Wang, Guo-Ming (Inorganic chemistry, 2022)
The rational design of 2D polyoxometalate-based metal–organic framework (POMOF) nanosheets on a conductive substrate as a self-supporting electrode is highly attractive but a great challenge. Herein is the first demonstration of POMOF nanopillar arrays consisting of 2D nanosheets as a self-supported electrode for the hydrogen evolution reaction (HER) in acidic conditions. Single-crystal X-ray analysis reveal that our as-prepared 2D [Co2(TIB)2(PMo12O40)]·Cl·4H2O [named CoMo-POMOF; TIB = 1,3,5-tris(1-imidazoly)benzene] crystalline materials are connected by Co-α-Keggin polymolybdate units act as secondary building blocks and TIB as the organic ligands. The 2D CoMo-POMOF nanosheets were successfully arrayed on a conductive nickel foam substrate by a facile CoO nanorod template-assisted strategy. Remarkably, the CoMo-POMOF nanopillar arrays demonstrate superior electrocatalytic performance toward the HER with an overpotential of 137 mV and Tafel slope of 59 mV dec–1 at 10 mA cm–2, which are comparable to those of state-of-the-art POMOF-based electrocatalysts. Density-functional theory (DFT) calculations demonstrate that the exposed bridging oxygen active sites (Oa) of Co-α-Keggin polymolybdate units in CoMo-POMOF optimize the Gibbs free energy of H* adsorption (ΔG H* = −0.11 eV) and increase the intrinsic HER activity.